ESG-Sharia Integration as a Determinant of Stock Performance Superiority: Evidence from the Jakarta Islamic Index 2024-2025 - Sigit Santoso; Budi Sukardi (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the performance of sharia stocks included in the Jakarta Islamic Index (JII) on the Indonesia Stock Exchange during the 2024-2025 period. The phenomenon of sharia capital market growth reaching 22.81% year-to-date in August 2025 demonstrates the crucial role of Islamic principle-based investment in facing global market volatility. Using a quantitative approach, this research evaluates returns, volatility, and factors influencing sharia stock performance through analysis of five selected stocks (BRIS, UNVR, TLKM, ANTM, ADRO) from December 2024 to May 2025. The results indicate that sharia stocks in JII offer competitive returns with varying volatility, where TLKM shows the lowest volatility (8.39%) while ANTM and UNVR exhibit high volatility (21.26% and 29.41%). A surprising finding reveals that sharia stocks with lower volatility do not always provide optimal returns, yet offer superior stability compared to conventional stocks, especially during economic uncertainty. This study contributes a new perspective that integration of sharia compliance with ESG sustainability has proven to enhance long-term financial performance, challenging the conventional view that ethical investment sacrifices profitability. The research implications provide strategic recommendations for investors to diversify portfolios based on risk-adjusted returns, regulators to strengthen the ESG-Sharia framework, and issuers to increase sharia governance transparency to optimize the competitiveness of Indonesia's sharia capital market.